Influence of Price, Promotion, and Service Quality On Consumer Purchasing Decisions at Geprek Sa’i Chicken - Mukhamad Masykur Hadi; Mochamad Rizal Yulianto; Satrio Sudarso (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to examine the influence of price, promotion, and service quality on consumer purchasing decisions at Ayam Geprek Sa'i. Methodology: The research used a quantitative method with a descriptive approach. The sample consisted of 100 respondents who were consumers of Ayam Geprek Sa'i and had made purchases more than once. The sampling technique used was purposive sampling, and data were collected through a questionnaire measured using a Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software. Results: The results showed that price and promotion had a positive and significant effect on consumer purchasing decisions. Price was the most dominant variable influencing purchasing decisions, while promotion had a smaller but still significant effect. Meanwhile, service quality did not have a significant effect on purchasing decisions. The R-square value of 0.539 indicates that price, promotion, and service quality explain 53.9% of purchasing decisions, while the remaining percentage is influenced by other variables not included in this study. Findings: The findings of this study indicate that price and promotion have a positive and significant effect on consumer purchasing decisions at Ayam Geprek Sa’i. Price was found to be the most dominant factor influencing purchasing decisions, while promotion also contributed significantly with a smaller effect size. In contrast, service quality did not show a significant effect on purchasing decisions. Additionally, the model explained 53.9% of the variance in purchasing decisions, indicating that other factors outside the study also influence consumer behavior. Novelty: The novelty of this study lies in examining the influence of price, promotion, and service quality simultaneously on purchasing decisions at Ayam Geprek Sa’i, with findings showing that price is the most dominant factor while service quality has no significant effect. Originality: The originality of this study lies in analyzing purchasing decisions at Ayam Geprek Sa’i by examining the combined effect of price, promotion, and service quality, with findings that identify price as the dominant factor and service quality as non-significant. Conclusion: In conclusion, price and promotion have a positive and significant effect on purchasing decisions at Ayam Geprek Sa’i, while service quality has no significant effect. Price was identified as the most dominant factor influencing consumer purchasing decisions. Type of paper: Quantitative research article.